Lenocinium, Avaritia, Hiems – stara kobieta w wizerunkach postaci symbolicznych w „De actione scenica” Franza Langa w świetle tradycji literackiej i artystycznej - Zaborowska-Musiał, Justyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The article focuses on the analysis of the role and importance of the theme of old woman in several allegorical images proposed by the Jesuit lecturer, playwright, and author of theatrical performances and drama theatre theorist, Franz Lang in his very important (it marked an high point of his dramatic output) handbook of acting De actione scenica published in Munich in 1727.